A Novel Approach to the Management of Children with Primary Nocturnal Enuresis - Agar, Buket Esen; Gurgoze, Metin Kaya; Kara, Aslihan (Mdpi, 2025)
Background/Objectives: Primary nocturnal enuresis (PNE) is a common condition that adversely affects the quality of life of both children and their families. It is known to have a multifactorial pathogenesis. This study aimed to evaluate serum levels of 25-hydroxyvitamin D (25OHD), vitamin B12, folic acid, and ferritin in children diagnosed with PNE and to investigate the impact of correcting detected deficiencies on the number of wet nights. Methods: A total of 150 pediatric patients diagnosed with monosymptomatic primary nocturnal enuresis (PNE) who had previously undergone standard urotherapy without clinical improvement were included in this study. Serum levels of vitamin B12 and 25-hydroxyvitamin D (25OHD) were assessed, and patients with deficiencies were identified. Vitamin supplementation was administered to those with deficient/insufficient levels. The number of wet nights was recorded at monthly follow-up visits to monitor clinical response. Results: Only 14% of the 150 patients had no detectable vitamin deficiencies. A deficiency in serum vitamin B12 levels was observed in 78.6% of patients, while 41.3% had reduced 25-hydroxyvitamin D (25OHD) levels. Concurrent deficiencies in both 25OHD and vitamin B12 were detected in 34% of the patients. No folate deficiency was observed in any patient. Notably, vitamin supplementation alone resulted in successful enuresis management in 77.6% of the patients. Conclusions: A high prevalence of vitamin B12 and 25-hydroxyvitamin D (25OHD) deficiencies was identified among patients diagnosed with primary nocturnal enuresis (PNE). Significant improvements in nocturnal dryness were achieved solely through correction of these deficiencies, without the use of desmopressin therapy. These findings suggest that targeted vitamin supplementation may play a crucial role in enhancing the success rate of standard urotherapy in the management of PNE.
Keywords: child; enuresis; vitamin B12; 25-hydroxyvitamin D